THE REFUSAL STRATEGIES EMPLOYED BY PRE-SERVICE EFL TEACHERS: A COMPARISON BETWEEN JAVANESE AND SUMATRANS - Lintang Indah Ayu Respati Dewi; Lailatun Nurul Aniq; Khairani Dian Anisa (Jurnal Penelitian Humaniora, 2020)
Refusing is a part of commissive speech acts. Refusing is a face-threatening act (FTA) that needs a good pragmatic competence since it probably gives risk to the interlocutor's positive or negative face. However, it indicates that people from various cultural backgrounds employ dissimilar refusal strategies. This study aimed at providing a comparison of refusal strategies used between Javanese Pre-service English Teachers (JPETs) and Sumatranese Pre-service English Teachers (SPETs) in accordance with different levels of power. The data were elicited from the DCT given to 10 JPETs and 10 SPETs. The participants were asked to fill the DCTs with written responses in which each DCT described different contexts and settings. Based on the analysis, JPETs and SPETs employed similar strategies in refusing to a request. The difference was only on the frequency usage of a certain strategy. Furthermore, all of the indirect strategies were applied to refuse a request meanwhile only a strategy comes from a direct strategy called the negation of proposition that is applied. A direct refusal strategy call bluntness was not applied. This study evoked pre-service awareness of pragmatic competence which could be taught to their future students and larger participants were encouraged for future study.